Analisis Pengaruh Wash (Water, Sanitation and Hygiene) terhadap Kejadian Stunting pada Balita - Wahyu Ilahi; Yayat Suryati; Noviyanti Noviyanti; Henny Suzana Mediani; Fauziah Rudhiati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effect of WASH (Water, Sanitation, and Hygiene) related to the incidence of stunting in children under five in the working area of ​​the Pangkajene City Health Center. The research method used in this study was a quantitative method with a case-control research design. The results showed that there was a relationship between drinking water sources (OR 5,417, p=0,007), drinking water treatment (OR 11,027, p=0,001), physical quality of drinking water (OR 7,207, p=0,001), and latrine ownership (OR 7, 4241, p=0.001) waste management (OR 4.151, p=0.007), waste management (OR 4.313, p=0.002) on stunting. Hygiene (OR 3,208, p=0.051) did not have a relationship with the incidence of stunting in the working area of ​​the Pangkajene City Health Center. The most dominant factors are latrine ownership (OR 6,289) and waste management (OR 5,124). In conclusion, there is a relationship between drinking water sources, water treatment, physical quality of drinking water, latrine ownership, waste management, and waste management on stunting. Keywords: Toddler, Hygiene, Sanitation, Stunting, Water